Elucidating trends and underlying drivers of neonatal mortality stagnation in Nepal: An analytical perspective on the 2016 and 2022 Demographic and Health Surveys - Khem Narayan Pokhrel; Resham Khatri; Suman Sapkota; Kalpana Gaulee Pokhrel; Gauri Pradhan; Tulsi Ram Thapa; Kamal Prasad Chapain; Thomas Pullum; Fern Greenwell (PLoS ONE, 2025)
Background Nepal has made significant progress in reducing the Neonatal Mortality Rate (NMR) over the past two decades. However, since 2016, NMR has stagnated at 21 deaths per 1,000 live births, indicating stalled improvements in neonatal survival. Past studies highlighted the disparities, with socioeconomically disadvantaged groups experiencing a higher rate of neonatal deaths. However, limited evidence exists on NMR trends and determinants in Nepal that examined the factors with the trend. This study analyzed NMR trends and key determinants using data from the two most recent Nepal Demographic and Health Surveys (NDHS). Methods NDHS 2016 and NDHS 2022 data were used to calculate NMR. Both surveys received ethical approval from the Nepal Health Research Council. The study included 106 neonatal deaths out of 5,087 live births in 2016 and 105 out of 5,192 in 2022. Independent variables included household characteristics, parental factors, pregnancy-related factors, maternal and newborn care, women’s empowerment, and health system factors. NMRs were constructed using births within completed months from 1 to 61. A general linear model assessed NMR trends, while logit regression identified key determinants. Results While national NMR remained unchanged since 2016, an increasing trend was observed among disadvantaged groups and mothers who did not utilize maternal/newborn health services. NMR rose from 27.3 to 27.8 per 1,000 live births (p = 0.001) among poor and poorest households. Similarly, women with no education experienced higher NMR at 29.3% in 2022 compared to 25.7% in 2016 (p = 0.002). Maithili-speaking mothers had higher NMR (27.4 in 2022 vs. 23.4 in 2016, p < 0.001). Women lacking decision-making power in healthcare had higher NMRs of 25.9 in 2022 vs. 23.4 in 2016 (p = 0.021). Women who were not assisted by skilled birth attendants (SBA). had significantly higher NMR compared to those, who were assisted by SBA (p = 0.010). Conclusions Targeted health system interventions are needed for disadvantaged groups covering those who had low education, from poor households, low health care decision making and lack access to SBA assisted delivery. While determinants have been explored, further targeted studies are warranted to uncover the causes of neonatal deaths in Nepal.